The King Edward Point Geodetic Observatory, South Georgia, South Atlantic Ocean: A First Evaluation and Potential Contributions to Geosciences - TEFERLE, Felix Norman; HUNEGNAW, Addisu; AHMED, Furqan; SIDOROV, Dmitry; Woodworth, Philip L; Foden, Peter R; Williams, Simnon P D (Springer, 2016)
peer reviewed During February 2013 the King Edward Point (KEP) Geodetic Observatory was established in South Georgia, South Atlantic Ocean, through a University of Luxembourg funded research project and in collaboration with the United Kingdom National Oceanography Centre, British Antarctic Survey, and Unavco, Inc. Due to its remote location in the South Atlantic Ocean, as well as being one of few subaerial exposures of the Scotia tectonic plate, South Georgia Island has been a key location for a number of global monitoring networks, e.g. seismic, geomagnetic and oceanic. However, no permanent geodetic monitoring station has been established previously, despite the lack of observations from this region. In this study we will present an evaluation of the GNSS and meteorological observations from the KEP Geodetic Observatory for the period from 14 February to 31 December 2013. We calculate multipath and positioning statistics and compare these to those from IGS stations using equipment of the same type. The on-site meteorological data are compared to those from the nearby KEP meteorological station and the NCEP/NCAR reanalysis model, and the impact of these data sets on integrated water vapour estimates is evaluated. We discuss the installation in terms of its potential contributions to sea level observations using tide gauges and satellite altimetry, studies of tectonics, glacio-isostatic adjustment and atmospheric processes. New Geodetic Infrastructure and Reprocessed GPS Solutions for Sea Level, Climatology and Geodynamics (GSCG)